Model Mineralisasi Pembentukan Opal Banten - Ansori, Chusni (Geological Agency, 2010)
DOI: 10.17014/ijog.v5i3.100Opal is a beautiful precious gemstone that is equal or more valuable than diamond. In Indonesia, precious opal is found at the Lebak Regency, Province of Banten. Banten’s opal widely has been recognized due to its beautiful opalescence. This paper is a review of the last research; preliminary study of Banten’s opal, characteristics of opal-CT and determining of opal type from geochemical data, added by new data to compile concept and to make mineralization model. In order to fulfill these targets, field geology research and analysis of mineralog/gemology, petrography, X-RD, and major and trace element geochemistry have been done. The Banten’s opal is opal-CT showing opalescence (play of colour), weathering, and leaching silica from volcanic glass by dark grey claystone hosted. Mineralization model is divided into three periods; at Early Pliocene volcanic clastic sediments rich in volcanic glass occured as fluvial sediments. Afterwards, at Late Pliocene - Pleistocene folding, weathering and leaching of silica took place. Intensive jointing, faulting, and folding quickened weathering and leaching processes to formed opal at limb of anticline through Holocene. The prospecting area of Banten’s opal is in tuff unit with intercalation of conglomerate or pumiceous breccia, at limb of anticline. The host rock of opal is dark grey claystone which underlies polimict conglomerate/pebbly sandstone sequence with cross stratification, imbricated, and erossional stucture; more than 8 m deep.